Achieving high seroprevalence against polioviruses in Sri Lanka—Results from a serological survey, 2014. (December 2015) - Gamage, Deepa; Palihawadana, Paba; Mach, Ondrej; Weldon, William C.; Oberste, Steven M.; Sutter, Roland W.
Abstract: The immunization program in Sri Lanka consistently reaches >90% coverage with oral poliovirus vaccines (OPV), and no polio supplementary vaccination campaigns have been conducted since 2003. We evaluated serological protection against polioviruses in children. A cross-sectional community-based survey was performed in three districts of Sri Lanka (Colombo, Badulla, and Killinochi). Randomly selected children in four age groups (9–11 months, 3–4 years, 7–9 years, and 15 years) were tested for poliovirus neutralizing antibodies. All 400 enrolled children completed the study. The proportion of seropositive children for poliovirus Type 1 and Type 2 was >95% for all age groups; for poliovirus Type 3 it was 95%, 90%, 77%, and 75% in the respective age groups. The vaccination coverage in our sample based on vaccination cards or parental recall was >90% in all age groups. Most Sri Lankan children are serologically protected against polioviruses through routine immunization only. This seroprevalence survey provided baseline data prior to the anticipated addition of inactivated poliovirus vaccine (IPV) into the Sri Lankan immunization program and the switch from trivalent OPV (tOPV) to bivalent OPV (bOPV).